Experimental and numerical prediction of wetting fronts size created by sub-surface bubble irrigation system - Alrubaye, Yasir L.; Yusuf, Badronnisa; Mohammad, Thamer A.; Nahazanan, Haslinda; Mohamed Zawawi, Mohamed Azwan (Multidisciplinary Digital Publishing Institute, 2022)
A bubble irrigation system (BIS) is a subsurface irrigation method recently introduced that may provide a better mechanism in terms of flow regulation, as it involves mainly the exchange of water and air bubbles under slight negative pressure. The negative pressure flow was created using inverted closed plastic bottles (ICPB) that connected to an elevated closed tank. Understanding the characteristics of wetting fronts is key in designing this irrigation system. This paper mainly presents the principles of BIS, the experimental measurements and software simulation of BIS wetting patterns, and the development of statistical models for BIS wetting patterns dimensions estimation. Laboratory experiments were accomplished to measure the BIS’s sharp-wetting fronts variation with four diameters of contact areas of ICPB and two different soil types, namely SS1 and SS2. In addition, numerical simulations using a 2D HYDRUS were performed to explore the possibility of using the simulated non-sharp wetting fronts in predicting BIS wetting fronts. The experimental results and numerical simulations show that the soil properties and the area of contact have a significant impact on the bubble flow rate and the shape and size of the wetting patterns. The hydraulic conductivity and the density of soil SS2, which were 62 and 22 percent, respectively, higher than soil SS1, have resulted in average incremental ratios of wetted depth and width by 94 and 178 percent, respectively. Results also show that more than 50 percent of the growth of wetting fronts’ width and depth occurred rapidly at the early portion of irrigation time before flattening at the latter time, indicating the effectiveness of the air–water exchange in regulating the amount of water supplied and in controlling wetting fronts propagation. Furthermore, based on experimental and simulation results, regression models have been developed for estimation of bubble flow rates and the size of wetting fronts. The developed models can be reliably used to predict the bubble flow rate and size of wetting patterns with high accuracy.